Effects of Lee Silverman Voice Treatment BIG and conventional physiotherapy on non-motor and motor symptoms in Parkinson’s disease: a randomized controlled study comparing three exercise models - Schaible, Fabian (Ther Adv Neurol Disord, 2021)
BACKGROUND: Parkinson’s disease (PD) patients experience disabling motor dysfunctions as well as non-motor symptoms (NMSs) that can highly impact their perceived quality of life. Besides pharmacological treatment options, active intervention programs have set some attention in managing these symptoms. However, previous studies mainly assessed the effectiveness of active intervention programs on functional mobility and motor symptoms. OBJECTIVE: This study aimed to investigate the effect of Lee Silverman Voice Treatment (LSVT) BIG, an intensified and personalized physiotherapy (INTENSIVE), and a conventional physiotherapy (NORMAL) on NMSs in PD. METHOD: Forty-four patients with mild to moderate PD were randomly assigned to one of the three treatment groups. LSVT BIG and INTENSIVE were delivered one-on-one in 16 1-hour sessions within 4 weeks (4×/week). Patients assigned to NORMAL received 16 individual 1-hour sessions within 8 weeks (2×/week). The primary outcome measure was the difference in change from baseline in the non-motor symptom assessment scale for Parkinson’s disease (NMSS) between treatment groups to follow up at week 8. Patients were blinded for the NMSS being the primary outcome, but not the different treatment groups. RESULTS: ANCOVA (Analysis of Covariance) showed reduced NMSS scores for all groups, with INTENSIVE being superior to NORMAL (p = 0.033). For secondary outcome measures (stride length, gait velocity and chair rising test) LSVT BIG and INTENSIVE were both superior to NORMAL. CONCLUSIONS: The study provides evidence that all three exercise programs are effective techniques to improve NMSs as well as motor function in PD. DRKS REGISTRATION NUMBER: DRKS00008732